2013
DOI: 10.5433/1679-0359.2013v34n2p649
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphate fertilization on phosphorus levels in foliage and tuber yield of the potato cv. Ágata

Abstract: The healthy development of potato tubers requires, among other agricultural practices, proper fertilization. Potato crops require large amounts of nutrients, and therefore consume a large amount of fertilizer. In Brazilian soils, phosphorus is the nutrient that produces the highest response in tuber yields. The objective of this work was to study the effect of different levels of phosphorus fertilizer on the potato cultivar Ágata, by evaluating foliar levels of phosphorus and tuber yield under field conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 4 publications
1
25
1
5
Order By: Relevance
“…Phosphorus fertilization linearly increased the leaf P concentration in the sandy soil, but in the clayey soil, the increases in leaf P concentration occurred only up to the estimated rate of 151 mg dm -3 P ( Figure 1a). Luz et al (2013) observed a reduction in leaf P concentration in the potato cultivated in clayey soil, with an increase in P supply, although the P availability in the soil increased. In the lower and higher P rates, the P concentration in the leaves of the potatoes cultivated in the sandy soil was higher than in the potatoes cultivated in the clayey soil, possibly due to relatively higher increase in P availability in the sandy soil compared to the clayey soil.…”
Section: Resultsmentioning
confidence: 97%
“…Phosphorus fertilization linearly increased the leaf P concentration in the sandy soil, but in the clayey soil, the increases in leaf P concentration occurred only up to the estimated rate of 151 mg dm -3 P ( Figure 1a). Luz et al (2013) observed a reduction in leaf P concentration in the potato cultivated in clayey soil, with an increase in P supply, although the P availability in the soil increased. In the lower and higher P rates, the P concentration in the leaves of the potatoes cultivated in the sandy soil was higher than in the potatoes cultivated in the clayey soil, possibly due to relatively higher increase in P availability in the sandy soil compared to the clayey soil.…”
Section: Resultsmentioning
confidence: 97%
“…At low pH, M3 is expected to be highly efficient at extracting Al-related P (Figure 2), likely due to the use of an acidic and fluoride-rich extraction solution, yet at low pH levels, Al-P is poorly water soluble [22], which will be reflected in plant availability [57], coinciding with the minimum water solubility (Figures 1, 6 and 7). This could help explain the common observation that potatoes often respond to P fertilizer, even under conditions where soil test P is optimum [58], as potatoes are mostly grown in fairly acidic soils. Mehlich-3 is generally a poor extractor of Fe compared to Al, partly due to the lack of complex formation with F − and short reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…Em solos com baixa disponibilidade de P, outros autores obtiveram aumentos maiores na produtividade de tubérculos, que variaram de 42% (BOOCK & FREIRE, 1960;FONtES et al, 1997) a 112% (ALvAREz-SáNCHEz et al, 1999. Contudo, tanto em solo de baixa como de alta disponibilidade inicial de P, os incrementos na produtividade de tubérculos observados com a aplicação de doses acima de 500kg ha -1 de P 2 O 5 foram pequenos, ou seja, entre 2,5 e 7,0% (NAvA et al, 2007;LUz et al, 2013). Neste estudo, a aplicação de doses maiores que 300 kg ha -1 de P 2 O 5 não alterou a produtividade de tubérculos comercializáveis nas duas condições de disponibilidade de P no solo, porque não afetou a massa média de tubérculos (Figuras 1a e 1b).…”
Section: Resultsunclassified
“…tubérculos grandes e com formato redondo (PáDUA, 2010), com elevado peso específico (HOCHMUtH et al, 2002), alta porcentagem de matéria seca (MS) e baixo teor de açúcares redutores (PEREIRA et al, 2007;PáDUA, 2010) Devido ao fato de a batateira ser considerada como exigente em nutrientes (FERNANDES et al, 2011), na maioria das vezes, essa cultura recebe elevadas doses de fertilizantes, a fim de garantir elevados níveis de produtividade (QUADROS et al, 2009;FERNANDES & SORAttO, 2012a), muitas vezes, sem se atentar para as características de qualidade dos tubérculos. Entre os fertilizantes utilizados no cultivo da batata, os fosfatados se destacam pelas elevadas doses que são aplicadas no momento do plantio (FERNANDES & SORAttO, 2012b) e pelo fato de ser o nutriente que oferece as maiores respostas de produtividade nos solos brasileiros (LUz et al, 2013).…”
Section: Introductionunclassified